A CASE REPORT OF SHIROBASTI IN THE MANAGEMENT OF DARUNAKA WITH SPECIAL REFERENCE TO DANDRUFF - Kumar Pankaj; Chauhan Vikas; Sinha Kaushal; BA Lohith (International Journal of Applied Ayurved Research, 2017)
Shirobasti comes under one of the four Murdhani taila, which are basically used for the management of Shiro roga and Urdhwa jatrugata roga. While explain the importance of shiro basti it is mentioned that it is useful in the management of Ardita, Ratri jagarana, Nasa-Mukha shosha, Timira, Shiroroga, Darunaka etc. It is best among the four Murdhani taila procedures. As dandruff is the shedding of the dead skin cells from the scalp, it is the common scalp disorder affecting almost half of the population at the post-pubertal age and of any sex and ethnicity. It affects half of the adult population throughout the globe. And in Ayurveda it is correlated with Darunaka. Here is a case report of dandruff where a male patient aged about 23 years c/o itching of scalp, hair fall, flakes over the head and shoulder. He approached SDM college of Ayurveda & hospital Hassan and got OPD base treatment. After the course of treatment there was marked improvement on symptoms like itching of scalp, hair fall, flakes.